Beyond PTSD and Fear-Based Conditioning: Anger-Related Responses Following Experiences of Forced Migration—A Systematic Review - Tuomisto, Martti T.; Roche, Jane E. (Frontiers in Psychology, 2018)
Experiences of forced migration include traumas that are interpersonal in nature, as well as ongoing emotional responses, stress and frustration in post-migration settings. Open questions exist, regarding anger/anger-like responses following experiences of persecution and ongoing stress. The aim of this study was to explore the adaptive and maladaptive underlying mechanisms of anger/anger-like responses, cultural, linguistic, and social contingencies, and possible interventions for problematic anger behavior. Method. We searched two databases (PsycINFO and PILOTS) with the following search terms: (refugee OR "asylum seek*" OR IDP OR "internal* displac*" OR "forced migra*" OR "involuntary migra*") AND anger. Findings. This search yielded 34 studies that were included in the final review. Although anger is a moral, adaptive, and prosocial response, dysfunctional anger/anger-like responses arise from PTSD, “moral injury,” complicated grief, and independent forms of anger behavior. Cultural, linguistic, and social issues also emerged from the search. Finally, considerations for treatment and intervention are discussed. Discussion. Anger responses following experiences of forced migration may require assessment beyond PTSD models currently framed by DSM and ICD. A very promising framework is the Adaptation and Development after Persecution and Trauma (ADAPT) model. Implications. Further longitudinal and epidemiological research will be necessary to continue testing the ADAPT model and to begin the process of assessing its cross-cultural coherence in other refugee populations (e.g., see Hinton et al., 2003). As anger behavior is also a societal issue, avenues for reconciliation, expression of grievances, employment, civic participation, and integration are needed.